Praktik Sewa Menyewa Hotel Melalui Aplikasi Online: Tinjauan Hukum Positif - Muhammad Ridha (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2024)
This study aims to analyze the practice of renting through online applications based on positive law. The research method used is descriptive analysis with a qualitative approach, which enables an in-depth understanding of the phenomenon within the context of positive law and Islam. Primary data was obtained from main literature such as legal books, hadiths, and documents discussing rental agreements according to positive law and Islam, while secondary data consists of journals, articles, and other relevant sources. Data collection was conducted through library research. The results of the study indicate that applications such as Pegipegi, Traveloka, and Agoda have successfully provided ease and transparency in hotel reservations with efficient procedures, although there are differences in cancellation policies and refund terms. These applications focus on customer satisfaction by providing clear information regarding the applicable terms and conditions. From the perspective of positive law, these applications comply with the provisions outlined in the Indonesian Civil Code, including personal data protection and adherence to valid operational permits. However, challenges in the implementation of cancellation policies and consumer rights protection still need attention. This study provides insights into how online rental applications can operate in accordance with existing legal regulations, as well as the challenges that arise in the digital era.